Residuos de plaguicidas organoclorados en rhizophora mangle y avicennia germinans en la ciénaga grande de santa marta, caribe colombiano (1998)
Residues of the organochlorine compounds lindane, heptachlor, aldrin, pp'DDE, pp'DDD y pp'DDT were determined in leaves of two species of mangrove (Rhízophora mangle and Avícennía germínans) from the Ciénaga Grande de Santa Marta. Samples were made quarterly (between March and December 1993), at tour stations at the Ciénaga and at one station in Bahía de Chengue (Parque Nacional Natural Tayrona). Measurements were made usinq gas-liquid chromatography. In both ecosystems the two species are accumulating all the six cornpounds analyzed, as well as other indeterminate organochlorines. The greatest concentrations were found for lindane with maximum values of 15,9 ng/g (dry weight). For lindane, heptachlor and aldrin the concentrations were significantly different only between climatic periods. The highest concentrations were obtained for the dry season. The concentration factor by species was calculated and it was determined that the mangroves are accumulating organochlorine compounds in greatest proportion from sedimento.